Factors that shape large‐scale gradients in clonality - Hongxiang Zhang; Si‐Chong Chen; Stephen P. Bonser; Timothy Hitchcock; Angela T. Moles (Journal of Biogeography, 2023)
Aim Many plant species reproduce clonally. However, ecologists still have much to learn about the factors that shape large‐scale patterns in plant clonal growth and reproduction, especially in the southern hemisphere. We addressed this knowledge gap by quantifying relationships between reproductive mode and a suite of plant characteristics and environmental variables. Location Australia. Taxon Spermatophytes. Methods We used data for 914,456 species‐site combinations (including 4116 unique species) in Australia to quantify the bivariate relationships between the probability of species having clonal reproduction and four plant characteristics and 16 environmental variables, using phylogenetic logistic regressions. We also compared the relative effects across plant characteristics and environmental variables groups through principal component analysis and phylogenetic logistic regressions. Results The probability of species having clonal reproduction was much more strongly related to plant characteristics than to environmental variables. Short, herbaceous plants and monocots were more likely to have clonal reproduction and were more common in environments with low temperatures, low solar radiation, high moisture availability, high net primary productivity (NPP) and high soil organic carbon and nitrogen contents. Tall, woody plants and eudicots tended to have only sexual reproduction, and were more common in dry and soil impoverished environments. Main conclusions Our results advance the understanding of the factors that shape large‐scale patterns in plant reproduction strategy. For example, the fact that clonality is more common in shorter, herbaceous species suggests that clonality can be added to the suite of traits that align species on the fast‐slow continuum. The fact that clonal reproduction is more tightly correlated with moisture availability, NPP and soil nutrients than climatic extremes and variations suggests that clonal reproduction may be better understood as a strategy for population expansion in resource abundant sites than as a strategy for reproductive assurance under environmental stress.